Optimizing Digital Media to Enhance Learning Outcomes in Aqidah Akhlak: A Case Study at Madrasah Ibtidaiyah DDI Awang-Awang - Herniwati; Firman, Firman; Kaharuddin; Muhammad Saleh; Usman (IAIN Parepare, 2024)
This study aims to analyze the effectiveness of digital media in improving students' learning outcomes in the subject of Aqidah Akhlak at Madrasah Ibtidaiyah DDI Awang-Awang, Pinrang Regency. The research employs a Classroom Action Research (CAR) method, conducted in two cycles comprising the stages of planning, implementation, observation, and reflection. Digital media such as animated videos and interactive quizzes were utilized during the learning process. The results indicate a significant improvement in students' average scores, from 73.75 in the first cycle to 88.12 in the second cycle. These findings confirm that digital media not only enhance comprehension but also increase students' interest and active engagement in learning. However, the study highlights certain limitations, including a lack of in-depth discussion on potential challenges, such as limited technological access in certain areas, teacher readiness, and cultural resistance to technology in education. Future research is needed to address these challenges and explore the best methods for integrating digital technology into the curriculum.